Low-Skilled Jobs, Language Proficiency and Refugee Integration: An Experimental Study - Simon Ek; Mats Hammarstedt; Per Skedinger (Research Institute of Industrial Economics (IFN), 2021)
We study the causal effects of previous experience and language skills when newly arrived refugees in Sweden apply for job openings by means of a field experiment. Applications were sent from randomly assigned fictitious Syrian refugees with experience in jobs with low skill requirements and completed language training in Swedish to employers advertising low-skilled job vacancies. We find no evidence of sizeable effects from previous experience or completed language classes on the probability of receiving callback from employers. However, female applicants were more likely than males to receive a positive response. We conclude that previous experience and completed language training seem to provide at best a small positive signaling value when refugees apply for low-skilled jobs through formal channels.
Keywords: J15; J24; J61; 330; Integration of immigrants; Language skills; Job mobility